Experiments of the efficacy of tree ring blue intensity as a climate proxy in central and western China - Zheng, Yonghong; Shen, Huanfeng; Abernethy, Rory; Wilson, Rob (Biogeosciences, 2024)
This paper was funded by the China Scholarship Council (grant no. 202006275018), the National Natural Science Foundation of China (NSFC, project no. 41771227), and Key Technology Projects of the Hubei Provincial Company of the China National Tobacco Corporation (grant nos. 027Y2021-020 and 027Y2022-006). Rob Wilson was further funded by the NSF/NERC project (grant no. NE/W007223/1 – Understanding Trans-Hemispheric Modes of Climate Variability: A Novel Tree-Ring Data Transect spanning the Himalaya to the Southern Ocean). To investigate the potential value of tree ring blue intensity as a robust climate proxy in central and western China, four species from five sites were assessed. As well as latewood inverted blue intensity, we also examined earlywood blue intensity. To explore the sensitivity of using different extraction parameter settings using the software CooRecorder, seven percentile (P) variant settings for earlywood blue intensity and latewood inverted blue intensity were used, namely P50 : 50, P60 : 40, P70 : 30, P80 : 20, P85 : 15, P90 : 10, and P95 : 5. Age-dependent spline was used for all, and the positive trends were not retained. Correlation analysis was applied between the tree ring parameter chronologies and monthly/seasonal mean temperature, precipitation, and self-calibrated Palmer drought severity index variables. Linear regression was also used to further highlight the potential of developing climate reconstructions using these species. Only subtle differences were found between the different percentile extraction variants. As has been shown for many other Northern Hemisphere studies, latewood inverted blue intensity expresses a strong positive relationship with growing-season temperatures (the two southern sites explain almost 56 % of the temperature variance when combined). However, the low latitude of these sites shows an exciting potential for regions south of 30∘ N that are traditionally not targeted for temperature reconstructions. Earlywood blue intensity also shows good potential to ...